HUBUNGAN ANTARA KEPEMIMPINAN VISIONER KEPALA SEKOLAH DAN BUDAYA ORGANISASI DENGAN DISIPLIN KERJA GURU MADRASAH TSANAWIYAH NEGERI DI JAKARTA BARAT - Ivon Makkadamah (STKIP Pembangunan Indonesia Makassar, 2020)
this study intends to analyze the relationship between the visionary leadrship of headmasterand culture organization with the labour of disipline teacher on islamic state junior highschool teachers in west java. The reaserch was using survey methods. Target population inthis study a special civil servant teachers and many as 188 people and the affordablepopulation as many as 126 people. By using slovin formula to determine the population ataffordable so that the teachers sampled were 95 people. In determining the sample theauthers use a multi stage proporsional simple randem sampling. For the results of reseacrhcan be congcluded matters as follows : firtst, there is positive relationship between thevisionary leadership of headmaster with the labour of disipline teacher. Second, there ispositive relationship between the culture organization with the labour of disipline teacher.Third, there is positive relationship between the visionary leadership of headmasterand theculture organization jointly with the labour of disipline teacher.Keyword : visionary leadrship, culture organization, disipline teachers.